Novel fibrinogen-related protein with single FReD contributes to the innate immunity of Macrobrachium rosenbergii. Issue 82 (November 2018) - Han, Keke; Chen, Xuefeng; Wu, Lei; Zhang, Zhuoxing; Ma, Futong; Huang, Xin; Zhang, Yufei; Ren, Qian
Abstract: Fibrinogen-related proteins (FREPs) are widely found in vertebrates and invertebrates, and they play crucial roles in innate immunity. Here, a new FREP named as MrFREP was identified from giant freshwater prawn ( Macrobrachium rosenbergii ). The full-length cDNA of MrFREP measures 1649 bp in length and consists of a 1086 bp open reading frame encoding a polypeptide composed of 361 amino acids. The MrFREP sequence has a signal peptide with 20 amino acids and a fibrinogen-related domain (FReD) with 223 amino acids. Phylogenetic analysis showed that MrFREP was grouped with FREPs from Marsupenaeus japonicus and Litopenaeus vannamei . BLASTp results showed that it had 43% identity with a FREP from M. japonicus . The expression of MrFREP was higher in gills, intestine, and hepatopancreas than in hemocytes, heart, stomach, and muscles. The expression levels of MrFREP in gills and intestine were obviously upregulated after they were exposed to Vibrio parahaemolyticus or White spot syndrome virus infection. Recombinant MrFReD protein (rMrFReD) could bind to Gram-positive and Gram-negative bacteria and agglutinate the tested bacteria in the presence of calcium. rMrFReD demonstrated lipopolysaccharide and peptidoglycan binding activities. rMrFReD could accelerate the clearance of V. parahaemolyticus in vivo . These results suggested that MrFREP could function as a pattern recognition receptor contributing to the innate immunity of M. rosenbergii . Highlights: Novel fibrinogen-related protein was identified from M. rosenbergii, named as MrFREP. MrFREP was regulated by V. parahaemolyticus and WSSV. rMrFReD could recognize glycoconjugates, bind and agglutinate various bacteria. rMrFReD could accelerate the clearance of V. parahaemolyticus in vivo.